3D‐accelerated, stack‐of‐spirals acquisitions and reconstruction of arterial spin labeling MRI. Issue 4 (3rd November 2016) - Chang, Yulin V.; Vidorreta, Marta; Wang, Ze; Detre, John A.
Abstract : Purpose: The goal of this study was to develop a 3D acceleration and reconstruction method to improve image quality and resolution of background‐suppressed arterial spin‐labeled perfusion MRI. Methods: Accelerated acquisition was implemented in all three k‐space dimensions in a stack‐of‐spirals readout using variable density spirals and partition undersampling. A single 3D self‐consistent parallel imaging (SPIRiT) kernel was calibrated and iteratively applied to reconstruct each imaging volume. Whole‐brain (including cerebellum) perfusion imaging was obtained at 3‐mm isotropic resolution (nominal) using single‐ and 2‐shot acquisitions and at 2‐mm isotropic resolution (nominal) using four‐shot acquisitions, achieving effective acceleration factors between 5.5 and 6.6. The signal‐to‐noise (SNR) performance of 3D SPIRiT was evaluated. The temporal SNR (tSNR) of the cerebral blood flow (CBF) maps and the gray/white matter CBF ratios were quantified. Results: The readout of the arterial spin labeling (ASL) sequence was significantly shortened with acceleration. The CBF values were consistent between accelerated and fully sampled ASL. With shorter spiral interleaves and shorter echo trains, the accelerated images demonstrated reduced blurring and signal dropout in regions with high susceptibility gradients, resulting in improved image quality and increased gray/white matter CBF ratios. The shortened readout was accompanied by a corresponding decrease in tSNR. Conclusion: The 3D acceleration and reconstruction allow a rapid whole‐brain readout that improved the quality of ASL perfusion imaging. Magn Reson Med 78:1405–1419, 2017. © 2016 International Society for Magnetic Resonance in Medicine.